Chlorine Use In Produce Packing Lines - Mark A. Ritenour; Steven A. Sargent; Jerry A. Bartz (EDIS)
This document is HS-761, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication Date: November 2002.